Thinking with the Global South and Decolonizing Indigeneity: Indigenous and Peasant Struggles to Reclaim Spaces, Identities, and Futures in Cauca, Colombia - (:unkn) unknown (My University, 2017)
In this dissertation, I examine indigenous and rural identities and economic practices in Cauca, Colombia that are illustrative of Southern efforts to destabilize Western and European hegemonic histories, and reassert the plural worldviews and practices that persist to this day. The indigenous and peasant movements that I highlight problematize coloniality’s totalizing and universalizing tendencies to erase local specificity across the post-colonial world. I argue these efforts are collectively decolonial in their orientations, as they seek to decenter the centrality of Western experiences in favor of the plurality of worldviews that are thriving in the Global South. Employing ethnographic methods, I find that decolonizing indigenous post-secondary education forges unity across ethnic difference, celebrating the plurality of ways of relating to the world that exist among Cauca’s indigenous peoples today. Further, I argue that indigenous post-secondary education is better conceived of as a pluriversity that opens its classrooms and students to the world around them, yet is emplaced in the specific realities of each community. Decolonial struggles to reclaim and assert rural peasant economic identities in Cauca attempt to transcend colonial ethnic identities. These overlapping social movements are creating a space for peasant identities and economic practices that seek to ‘make aware’, ‘make visible’, and ‘dignify’ peasant economics by publicly asserting their ‘value’ as peasants. Finally, I find that interrelationships between Nature and economies have been undertheorized to primarily focus on Western capitalism as the driving force in creating nature. I develop the notion of a harmonious economy (economía armónica) to theorize how indigenous relationships to Mother Earth engender qualitatively different economies in Cauca. Taken together, these diverging and intersecting movements suggest that productive work can be done at the intersections of political ecology, diverse economies, and indigenous geographies in order to understand the wealth of decolonial efforts in Colombia’s Andean Highlands.
Keywords: Colombia; Decolonial; Global South; Indigenous Geographies; Peasant